The Importance of Bancassurance in Sales Management Process of Insurance Products (Analysis of Statistical Data since 2012–2018) - Stęplewska, Kinga (Journal of Finance and Financial Law, 2021)
The aim of the article is to present and evaluate the situation of bancassurance in Poland and establishing the importance of this channel in the sale of insurance products. The paper concerns on product distribution, which is a very important part of the activity of any enterprise. One of the insurance product distribution channels is bancassurance based on cooperation between banks and insurers. Methodology. To achieve the goal quantitative changes were analysed, as well as a review of the introduced legal solutions in relation to bancassurance. Data on the bancassurance market in Poland are presented in the article, including the number and sales structure in this channel since 2012 to 2018. Results of the research. The analysis made it possible to conclude that bancassurance is an important distribution channel for insurance products with high development potential. However, in the analysed period, sales through this channel showed a downward trend, which was mainly caused by the introduction of new recommendations and legal regulations concerning the distribution of insurance products.